(untitled) - ; Haidee Y. Jaramillo; Francisco E. Moreno-Garcia (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
Student-centered learning has been used as a teaching strategy. In addition, methodologies like project-based, active, problem-based, and experiential learning are available to improve the educational process. However, employing these strategies necessitates prior familiarity with the critical tenets of the applicable discipline. To facilitate communication between the demands of the workplace and the learning outcomes of the academy, this article examines the use of project-based integrated learning as an educational practice (formative research strategy) to integrate the institutional curriculum of the Mechanical Engineering program in the Virtual Instrumentation course and the requirements of skills that the industry today. Also, the course uses LabVIEW software, which enables the development of virtual instruments for monitoring, acquiring, and processing data. This study aims to connect to the program curse curriculum, considering that the students select a topic and then present the information to the class in an exposition. The outcomes demonstrate that all students employed different techniques to produce a workable prototype in just sixteen (16) weeks providing a viable solution related to mechanical engineering and that these projects improved their leadership, problem-solving, communication, and time management abilities.